Águas urbanas : áreas de preservação permanente (APPs) do Rio Poxim em Aracaju/SE - Oliveira, Ingrid Carvalho Santos (2020)
Permanent Preservation Areas - PPAs are regulated by the Federal Law nº 12.651 of 25/05/2012 and should be a concern in the urban master plans, due to their importance for the population’s quality of life and the maintenance of some ecosystems such as dunes, mangroves and sandbanks. This study aims to evaluate the socio-environmental sustainability in the Areas of Permanent Preservation (APPs) of the Poxim River. The choice of the spatial section of the research was due to the APPs of this river being bordered by populous neighborhoods that directly impact the Poxim River. The neighborhoods are: Jabotiana, Inácio Barbosa, Jardins, Coroa do Meio, Farolândia and São Conrado. To support the formulation of this research, used structuralist method based on the PER (Pressure-State-Response) model, and the methodology was divided and was built in three stages: document search; on-site work and data systematization, with different methodological procedures, from the collection of primary and secondary data, in different sources, including visits on-site and photographs. They seek to answer the hypothesis and questions raised, and to understand the current situation of the area of study to elaborate, subsequently, guidelines that can contribute to the environmental, economic and social sustainability of the stretches surveyed. It is understood that it is necessary to evaluate these areas, as they are responsible for contributing to the quality of life and well being of the population, in addition to participating in the regularization of ecosystem services. Among the results, it is highlighted that 15% of APPs in the spatial area are occupied: Jabotiana (13%), Inácio Barbosa (42%), Jardins (5,88%), Coroa do Meio (11,91%), Farolândia (7,29%) and São Conrado (10,90%); It is emphasized that 6,43% are protected areas by the municipality; 2,52% are areas facing squares and parks; and 0,61% is the amount directed to municipal agencies, focused on the environment. The biggest weaknesses of the study areas are: occupation in areas of APPs; few public Free Spaces focused on social practices; absence of maintenance of existing leisure and recreation areas; effluents directly into Poxim River; and little or no inspection and signage to protect environmentally fragile areas, depends on the stretch. As potentialities, initiatives (individual and collective) of practices aimed at Environmental Education stand out. It is expected that this study will advance academic limits and contribute by acting as an action plan in the creation and execution of public policies aimed at the Poxim River APPs and their surroundings.